Reduction of industrial iron pollution promotes phosphorus internal loading in eutrophic Hamilton Harbour, Lake Ontario, Canada - Markovic, Stefan; Liang, Anqi; Watson, Sue B.; Depew, David; Zastepa, Arthur; Surana, Preksha; Byllaardt, Julie Vanden; Arhonditsis, George; Dittrich, Maria (Environmental pollution (1987), 2019)
Diagenetic sediment phosphorus (P) recycling is a widespread phenomenon, which causes degradation of water quality and promotes harmful algal blooms in lakes worldwide. Strong P coupling with iron (Fe) in some lakes is thought to inhibit diagenetic P efflux, despite elevated P concentrations in the sediment. In these sediments, the high Fe content leads to P scavenging on ferric Fe near the sediment surface, which increases the overall P retention. Reduced external Fe inputs in such lakes due to industrial pollution control may lead to unintended consequences for sediment P retention. Here, we study sediment geochemistry and sediment-water interactions in the historically polluted Hamilton Harbour (Lake Ontario, Canada) which has undergone 30 years of restoration efforts. We investigate processes controlling diagenetic P recycling, which has previously been considered minor due to historically high Fe loading. Our results demonstrate that present sediment P release is substantial, despite sediment Fe content reaching 6.5% (dry weight). We conclude that the recent improvement of wastewater treatment and industrial waste management practices has reduced Fe pollution, causing a decrease in diagenetically reactive Fe phases, resulting in the reduction of the ratio of redox-sensitive P and Fe, and the suppression of P scavenging on Fe oxyhydroxides. [Display omitted] •We studied P in sediment in lake sediments subject to a reduction of Fe pollution.•Stable authigenic Fe(II) phases acted as an effective sediment P sink.•Reducing sediment Fe levels limits the surface sediment capacity to bind P.•The reduction of Fe loading accelerated the P recycling processes in the lake.•The internal P loading is within the range of the external P input. We delineated the processes controlling the sediment P dynamics in eutrophic Hamilton Harbour, a unique system undergoing the reduction of Fe industrial pollution.